2015
DOI: 10.1371/journal.pone.0131423
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Different Grades of Tropical Cyclones on Infectious Diarrhea in Guangdong, 2005-2011

Abstract: ObjectiveGuangdong province is one of the most vulnerable provinces to tropical cyclones in China. Most prior studies concentrated on the relationship between tropical cyclones and injuries and mortality. This study aimed to explore the impacts of different grades of tropical cyclones on infectious diarrhea incidence in Guangdong province, from 2005 to 2011.MethodsMann-Whitney U test was firstly used to examine if infectious diarrhea were sensitive to tropical cyclone. Then unidirectional 1:1 case-crossover de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…Increases in water temperature, precipitation frequency and severity, evaporation–transpiration rates, persistent humidity, and changes in coastal ecosystems increase the incidence of water contamination with harmful pathogens and chemicals, resulting in increased human exposure and waterborne disease (Ahmed, Scholz, Al‐Faraj, & Niaz, ; Alderman, Turner, & Tong, ; Davies et al., ; De Man et al., ; Dura et al., ; Gao, Zhang, Ding, Liu, & Jiang, ; Kang et al., ; Lin, Wade, & Hilborn, ; Phung et al., ; Wade, Lin, Jagai, & Hilborn, ). Flooding events in particular increased the incidence of the following three diseases: hepatitis A virus (Gao, Zhang, Ding, Liu, & Jiang, , Gao, Zhang, Ding, Liu, Wang, & Jiang, ), bacillary dysentery (Liu, Liu, Zhang, & Jiang, ; Liu, Li, et al., ; Lin, Wade, & Hilborn, ; Ni, Ding, Li, Li, & Jiang, ; Ni, Ding, Li, Li, Liu, & Jiang, ; Zhang, Ding, Liu, Zhang, & Jiang, ), and Campylobacter (Soneja et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Increases in water temperature, precipitation frequency and severity, evaporation–transpiration rates, persistent humidity, and changes in coastal ecosystems increase the incidence of water contamination with harmful pathogens and chemicals, resulting in increased human exposure and waterborne disease (Ahmed, Scholz, Al‐Faraj, & Niaz, ; Alderman, Turner, & Tong, ; Davies et al., ; De Man et al., ; Dura et al., ; Gao, Zhang, Ding, Liu, & Jiang, ; Kang et al., ; Lin, Wade, & Hilborn, ; Phung et al., ; Wade, Lin, Jagai, & Hilborn, ). Flooding events in particular increased the incidence of the following three diseases: hepatitis A virus (Gao, Zhang, Ding, Liu, & Jiang, , Gao, Zhang, Ding, Liu, Wang, & Jiang, ), bacillary dysentery (Liu, Liu, Zhang, & Jiang, ; Liu, Li, et al., ; Lin, Wade, & Hilborn, ; Ni, Ding, Li, Li, & Jiang, ; Ni, Ding, Li, Li, Liu, & Jiang, ; Zhang, Ding, Liu, Zhang, & Jiang, ), and Campylobacter (Soneja et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Climate change is expected to lead to an increased number of storms and typhoons and East China is one of the regions seriously affected by tropical storms (Lu and Zhao 2013). Previous research in Guangdong, South China, found that the landing of tropical cyclones not only causes substantial direct economic losses but also threatens human health (Kang et al 2015). Research has found that tropical cyclones increase the risk of transmitted infectious diseases (Zheng et al 2017).…”
Section: A Climate Change Impacts On Health: Storms and Typhoonsmentioning
confidence: 99%
“…Research has found that tropical cyclones increase the risk of transmitted infectious diseases (Zheng et al 2017). Study in Guangdong city between years 11 2005-2011 concluding that there is an increase on the infectious diarrhea incidents after tropical cyclones (Kang et al 2015). An assessment on the public health risks and impacts of a tornado in Funing, East China concluded that elderly (75-84 year group) was at the highest risk death (RR (relative risk) = 82.16; 95% CI (confidence interval) = 19.66, 343.33) and injury (RR = 31.80; 95% CI = 17.26, 58.61), and females were at 53% higher risk of death than males (RR = 1.53; 95% CI = 1.02, 2.29) ).…”
Section: A Climate Change Impacts On Health: Storms and Typhoonsmentioning
confidence: 99%
See 1 more Smart Citation
“…За даними систематичного огляду, Vibrio spp. (V.cholera), Leptospira spp., E.coli -патогени, які найчастіше викликають спалахи під час паводків в Азії [14]. Низкою досліджень було встановлено, що тайфуни мають більший вплив на рівень захворюваності на інші інфекційні діареї у порівнянні з тропічними штормами, в той же час на бацилярну дизентерію вплив катастроф був протилежним.…”
unclassified